Analisis Big Data Kesiapan Digital Global Menggunakan PCA dan FASTCLUS - Setiawan, Ariyono; Yudianto, Prima Yudha; Ika, Ni Made; Masdiyas, I Gede Susrama (DPPM Universitas Pelita Bangsa, 2025)
This study aims to identify global digital readiness patterns using an innovative big data approach by integrating Principal Component Analysis (PCA) and the FASTCLUS clustering algorithm. By analyzing 1,076 observations from 2000 to 2023, this study focuses on four key indicators: secure server deployment and ICT infrastructure index. Referring to the Digital Readiness Framework, this study positions digital infrastructure and cybersecurity as the foundation of national digital capacity. PCA results show that two main components explain 56.35% of the total variance, and the clustering process produces strong segmentation with Pseudo F = 1275.85 and R² = 70.4%. Three digital readiness clusters were successfully identified: advanced (4 countries), moderate (64 countries), and transitional (1008 countries), each exhibiting distinct infrastructure and digital index characteristics. This study contributes a replicable, globally scalable classification framework for comparing digital readiness across countries. Its originality lies in the integration of big data techniques and unsupervised learning into national digital readiness assessments. These findings are important for supporting data-driven digital policy formulation, particularly for developing countries in designing more precise and contextual ICT resource allocation strategies.